Effective Maxwell's equations in general periodic microstructures. Issue 13 (3rd October 2018) - Schweizer, B.; Urban, M.
ABSTRACT: We study the time harmonic Maxwell equations in a meta-material consisting of perfect conductors and void space. The meta-material is assumed to be periodic with period ; we study the behaviour of solutions in the limit and derive an effective system. In geometries with a non-trivial topology, the limit system implies that certain components of the effective fields vanish. We identify the corresponding effective system and can predict, from topological properties of the meta-material, whether or not it permits the propagation of waves.